Telling Your Story Through Art - Doyon, Natasha (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2025)
Tell your story through art was a community-engaged art project with seniors at the Cummings Center in the winter of 2024; it used art as a testimony to their lives. This visual essay shares what the participants made over 10 workshops, in which they generated images from their real and imagined selves. The mixed media pieces the participants created were aesthetic interventions (hooks, 1995) that merged the shapes of memories with forms that could be decisively forged through creating works of art. The materiality of paints, photographs, collages, and papers was key to igniting the link between the stories they carried within themselves and their present reality. They filled gaps in time by engaging with hybrid systems of touching photographs, binding matrilineal collages to larger narratives, confronting traumatic memories, and unearthing buried nostalgia that straddled the uneven terrain of grief, forgiveness, and joy.